The cognitive basis of the linguistic term In "Exploring the Terminology of Arts and Sciences" by Al-Tahanawi - الكردي محمّد; مالك ياسين (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The issue of terminology is one of the thorny issues that occupied the attention of scientists since an early time, as terminology constitutes the basis for any branch of human knowledge, and without it, sciences are not upright. Among these sciences are the sciences of the Arabic language, which began to be interested in with the advent of Islam, some scholars dealt with issues of grammar and morphology, and others dealt with issues of rhetoric, and issues of sound and poetry had a large share of the scholars’ concerns, and they tried – through their treatment of the issues of these linguistic sciences – to set controls and limits Idiomatic for every science of the Arabic language, and it was the first appearance of linguistic terms in the stomachs of these books, then some scholars took upon themselves the task of collecting these terms in a special book that collects them, and among these scholars Muhammad Ali Al-Tahanawi, who collected in his book “Exploring the Terminology of Arts and Sciences” idiomatic expressions for every science of the Arabic language. The sciences of religion, Sharia, logic, philosophy, Arabic language sciences, and other sciences. This research will be concerned with collecting the linguistic terms mentioned by Al-Tahanawi in his book "Exploring the Terminology of Arts and Sciences", and distributing them among their fields of knowledge, in order to reveal the encyclopedic culture of Al-Tahanawi on the one hand, and the extent of his interest in Arabic language sciences on the other hand, and to present statistical results for the terms of each linguistic field in the encyclopedia .